Introduction. Geopolitics and geoeconomics of food in a changing world (Desarrollo, Estado y Espacio, 2025)
Food is a central strategic axis of the international economic system due to its geopolitical and geoeconomic implications. The availability and price of food directly affect political stability, the capacity for capital accumulation, and international conflicts, among other factors. Added to this is a key scientific and technological dimension, which has enabled unprecedented productive expansions. Within this framework, South America and Latin America occupy a strategic position, marked by tensions, inequalities, and global disputes. Against the backdrop of these major issues, the Dossier entitled “Geopolitics and Geoeconomics of Food: Structural Relationships, Trends, and the Role of South America in the International Economic System” is presented. Its objective is to examine the global food system, structured across multiple scales and dimensions, paying particular attention to the role played by South America.
Keywords: Global Food System; Food Geopolitics; Geoeconomics; South America